2018
DOI: 10.3390/medicines5010010
|View full text |Cite
|
Sign up to set email alerts
|

Auricular Neuromodulation: The Emerging Concept beyond the Stimulation of Vagus and Trigeminal Nerves

Abstract: Neuromodulation, thanks to intrinsic and extrinsic brain feedback loops, seems to be the best way to exploit brain plasticity for therapeutic purposes. In the past years, there has been tremendous advances in the field of non-pharmacological modulation of brain activity. This review of different neurostimulation techniques will focus on sites and mechanisms of both transcutaneous vagus and trigeminal nerve stimulation. These methods are scientifically validated non-invasive bottom-up brain modulation technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 77 publications
0
47
0
2
Order By: Relevance
“…This technique is thought to induce compensatory responses, via basal forebrain/brainstem projections through central thalamus and hypothalamus, in distal fronto-parietal and striatal networks. 88 Invasive VNS involves the surgical implantation of a vagus nerve stimulator, using a current of 1-2 mA. Mechanisms of stimulation are similar to taVNS.…”
Section: Vagal Nerve Stimulation (Vns)mentioning
confidence: 99%
“…This technique is thought to induce compensatory responses, via basal forebrain/brainstem projections through central thalamus and hypothalamus, in distal fronto-parietal and striatal networks. 88 Invasive VNS involves the surgical implantation of a vagus nerve stimulator, using a current of 1-2 mA. Mechanisms of stimulation are similar to taVNS.…”
Section: Vagal Nerve Stimulation (Vns)mentioning
confidence: 99%
“…Neuromodulation therapies for GI and psychological pathologies are emerging. These include non‐ or minimally‐invasive stimulation of afferent parasympathetic nerve fibers that innervate the outer ear and project to brainstem NTS (He et al, ; Li & Wang, ; Mercante, Deriu, & Rangon, ; Peuker & Filler, ). In adolescents with functional abdominal pain disorders, a large placebo‐controlled trial demonstrated improvement in pain and functioning using a novel auricular percutaneous electrical nerve field stimulator (Kovacic et al, ).…”
Section: An Autonomic State Regulation Perspective On Treatment and Pmentioning
confidence: 99%
“…L'action de l'Auriculothérapie relève plus de la neuromodulation que de la stimulation [27], à l'image du nerf vague, nerf complexeb i-directionnel qui favorise l'homéostasie, face aux changements de l'environnement [16]. Ainsi, même si l'Auriculothérapie se base sur des fondements neuro-anatomophysiologiques solides et objectifs, son mécanisme d'action n'est pas encore complètement élucidé.E n particulier,l es représentations auriculaires du système nerveux central [7,27,28] ne sont pas encore scientifiquement validées.…”
Section: Discussionunclassified
“…Ceci s'explique en partie par le manque cruel d'études aun iveau de la zone auriculaire innervéep ar le PCS.C ette zone auriculaire, la plus importante par la superficie, est largement sous-étudiée [ 28]. En effet, l'extrême majorité des études s'intéressentu niquement à la stimulation du nerf vague et utilisent la zone auriculaire du PCS comme une zone témoin.…”
Section: Discussionunclassified